Comprehensive analysis of latent reserves of innovative potential development - M. A. Korkin (Вестник университета)
The article provides a comparative analysis of the scientists’ and economists’ works, who studied the approaches to the methods of comprehensive assessment of latent reserves of innovation potential of the industrial complex. In the conditions of global economic relations transformation, the complex analysis of latent reserves of innovation potential development acts as one of the main elements of development and strategic growth of enterprises’ innovation potential. The conducted research has a significant impact on further study of the complex analysis of latent reserves of innovation potential development, contributing to the effective development of the industrial complex. The obtained results of the study can be used in the assessment and comprehensive analysis of latent reserves formation aimed at the enterprises’ innovative potential growth.